Bio-electrospraying assessment toward in situ chondrocyte-laden electrospun scaffold fabrication - Semitela, Ângela (2022)
Electrospinning has been widely used to fabricate fibrous scaffolds for cartilage tissue engineering, but their small pores severely restrict cell infiltration, resulting in an uneven distribution of cells across the scaffold, particularly in three-dimensional designs. If bio-electrospraying is applied, direct chondrocyte incorporation into the fibres during electrospinning may be a solution. However, before this approach can be effectively employed, it is critical to identify whether chondrocytes are adversely affected. Several electrospraying operating settings were tested to determine their effect on the survival and function of an immortalized human chondrocyte cell line. These chondrocytes survived through an electric field formed by low needle-to-collector distances and low voltage. No differences in chondrocyte viability, morphology, gene expression, or proliferation were found. Preliminary data of the combination of electrospraying and polymer electrospinning disclosed that chondrocyte integration was feasible using an alternated approach. The overall increase in chondrocyte viability over time indicated that the embedded cells retained their proliferative capacity. Besides the cell line, primary chondrocytes were also electrosprayed under the previously optimized operational conditions, revealing the higher sensitivity degree of these cells. Still, their post-electrosprayed viability remained considerably high. The data reported here further suggest that bio-electrospraying under the optimal operational conditions might be a promising alternative to the existent cell seeding techniques, promoting not only cells safe delivery to the scaffold, but also the development of cellularized cartilage tissue constructs.